The Role of Laser and Microwave in Treatment of Endocrine Disorders: A Systematic Review: Laser and microwave in endocrine disorders - Noghabaei, Giti; Ahmadzadeh, Alireza; Pouran, Fatemeh; Mahdavian, Amirmohsen; Rezaei, Mitra; Razzaghi, Mohammadreza; Mansouri, Vahid; Maleki, Farajolah (Journal of Lasers in Medical Sciences, 2024)
Introduction: The treatment of endocrine problems like thyroid disease, diabetes mellitus (DM), and polycystic ovary syndrome (PCOS) faces significant challenges so medical professionals worldwide are trying to find a new therapeutic approach. However, along with common treatments which include medications, hormone replacement therapy, and surgery; there is a growing interest in alternative therapies like laser therapy, which offers a non-invasive and unique technique for treating endocrine disorders alone or in combination with traditional methods. The main goal of this review was to do a systematic review of the role of the laser and Microwave in the treatment of endocrine disorders. Methods: In the present systematic review, the most important databases, including PubMed, Scopus, and Google Scholar were searched for studies examining the effect of lasers on the treatment of endocrine problems by using appropriate keywords and specific strategies from 1995 to 2023. All the studies that were not about lasers and endocrine were excluded. Results: Based on 51 reviewed studies, lasers and radiofrequency ablation such as RFA are effective in the treatment of thyroid diseases, hyperparathyroidism, pancreatic disorders, and sexual dysfunctions. Laser-induced interstitial thermal therapy (LITT) and microwave ablation (MWA) are genuine minimally invasive methods for the treatment of benign nodules, adenomas, and tumor ablation including pancreatic carcinomas and adrenal tumors. Intravenous laser blood irradiation (ILBI) which uses red, UV, and blue light could be effective in treating various metabolic disorders, such as DM. Conclusion: Laser as a cutting-edge and minimally invasive approach could treat various endocrine disorders. It has great potential to treat and regulate hormonal imbalances, decrease inflammation, and relieve symptoms of various ailments, such as endocrine disorders.